Regresyvinis minkštųjų priebalsių poveikis trumpųjų balsių spektrui bendrinėje lietuvių kalboje - Kliukienė, Regina (Kalbotyra, 2002)
As the spectral analysis showed, in Standard Lithuanian palatalised consonants have a great influence upon the spectrum of the preceding vowels [i], [u], [e] and [a]. The frequencies of the second formant (F2) change significantly in position [–C’]; the frequencies are much higher. The investigation results are presented in four tables. The research was carried out on a PC in the Laboratory of Experimental Phonetics of the Philological Faculty of Vilnius University.